Enhancing Return to Alpine Skiing: Integrating Perceptual-Motor-Cognitive Considerations in Testing and Progressions: A Clinical Commentary - Conor Smith; Dustin R. Grooms; Helen Bradley (International Journal of Sports Physical Therapy)
Alpine skiing poses significant risks for anterior cruciate ligament (ACL) injury at both recreational and professional levels, which is compounded by high rates of re-injury. Despite the existence of return to sport (RTS) and return to snow protocols, the frequency of ACL re-injury has not been mitigated, raising doubts about protocol effectiveness. Current RTS protocols primarily focus on biomechanical and neuromuscular factors in isolation, neglecting the important perceptual-motor-cognitive changes associated with ACL injuries and the high cognitive demands of skiing. The purpose of this clinical commentary is to address the perceptual-motor-cognitive demands specific to alpine skiing, evaluate RTS testing for skiers, and propose updated standards for testing and return to snow progressions that incorporate these considerations.